2005
DOI: 10.1016/j.neuron.2005.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Corelease of Dopamine and Serotonin from Striatal Dopamine Terminals

Abstract: The striatum receives rich dopaminergic and more moderate serotonergic innervation. After vesicular release, dopamine and serotonin (5-hydroxytryptamine, 5-HT) signaling is controlled by transporter-mediated reuptake. Dopamine is taken up by dopamine transporters (DATs), which are expressed at the highest density in the striatum. Although DATs also display a low affinity for 5-HT, that neurotransmitter is normally efficiently taken up by the 5-HT transporters. We found that when extracellular 5-HT is elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
170
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(179 citation statements)
references
References 46 publications
8
170
0
1
Order By: Relevance
“…Thus, our data indicate that chronic 5-HTT blockade partially depletes vesicular DA levels, which can be restored by systemic L-DOPA treatment. This vesicular DA depletion hypothesis is consistent with the crowding-out effect described after 5-HTT blockade, when 5-HT is taken up by the dopamine transporter (DAT) into DAergic neurons (Cases et al, 1998;Zhou et al, 2002Zhou et al, , 2005. Promiscuous 5-HT reuptake by the DAT can also explain the specific effect of 5-HTT blockade on striatal but not frontal cortex DA and DOPAC levels, because DAT immunoreactivity is high in the striatum and sparse in the frontal cortex (Sesack et al, 1998).…”
Section: -Ht Signaling and Daergic Control Of Bg Functionsupporting
confidence: 78%
“…Thus, our data indicate that chronic 5-HTT blockade partially depletes vesicular DA levels, which can be restored by systemic L-DOPA treatment. This vesicular DA depletion hypothesis is consistent with the crowding-out effect described after 5-HTT blockade, when 5-HT is taken up by the dopamine transporter (DAT) into DAergic neurons (Cases et al, 1998;Zhou et al, 2002Zhou et al, , 2005. Promiscuous 5-HT reuptake by the DAT can also explain the specific effect of 5-HTT blockade on striatal but not frontal cortex DA and DOPAC levels, because DAT immunoreactivity is high in the striatum and sparse in the frontal cortex (Sesack et al, 1998).…”
Section: -Ht Signaling and Daergic Control Of Bg Functionsupporting
confidence: 78%
“…In view of pH differences between vesicles and axoplasm, there could be at least a 100-fold increase in [ 3 H]5-HT vesicular concentration compared with the axoplasm (Njus et al, 1986), although this passively generated gradient remains very small compared with that generated by VMAT2, it may nevertheless be a way to compensate for VMAT2 loss. (3) Finally, there is evidence for uptake of 5-HT in catecholaminergic neurons (Cases et al, 1998;Zhou et al, 2005). Storage of [ 3 H]5-HT in any non-serotonergic neurons, still normally expressing VMAT2 in VMAT2 sertÀcre mice, could account for some of the [ 3 H]5-HT release observed here.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 5-HT can be taken up by transporters other than the 5-HTT, including the dopamine transporter (DAT) (Callaghan et al, 2005;Zhou et al, 2005) and norepinephrine transporter (NET) , and that DAT-mediated clearance of 5-HT is upregulated in the 5-HTTÏȘ/ÏȘ mice (Zhou et al, 2002). There is also evidence that ethanol can inhibit dopamine (Robinson et al, 2005) and norepinephrine (Lin et al, 1993(Lin et al, , 1997) uptake via effects on DAT and NET respectively.…”
Section: -Htt Inactivation Potentiates the 5-ht Clearance-inhibitingmentioning
confidence: 99%